Islam di Burma - Abu Haif (Jurnal Adabiyah: Humanities and Islamic Studies, 2016)
This paper is a literature review that is intended to see the development of Muslims since the arrival of Islam in Burma until modern times. The results of the literature review find the data that the Islamic religion brought by Muslim sailors who came to Burma in the ninth century. They then developed with trading activities in Southeast Asia and reached its peak until the seventeenth century, with a mastery of the coastal towns in Burma into the trading network wider Muslim. In addition to trade, they are also active in the manufacture and maintenance of the ship. In the field of culture, the Muslims of Burma a little different with the Burmese Buddhists. The Muslims of Burma continue to use the names of Burma, although they also use Muslim names that can be used in their own territory and the environment, the Muslims of Myanmar are increasingly different from those of Myanmar are Buddhist. Their culture tends to be influenced by the Muslim culture of India.